Life Cycle Cost Analysis of Building Maintenance - Rosita, Evita; Yustiarini, Dewi; Nurasiyah, Siti (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2023)
Building maintenance is an activity to maintain the reliability of the building so that it remains functional following the Regulation of the Minister of Public Works No. 24 / PRT / M / 2008 concerning Building Maintenance Guidelines; building maintenance includes architectural, structural, and mechanical maintenance. This problem must be considered during building construction to realize the use of structures that fulfil requirements for efficiency, environmental harmony, safety, health, comfort, and convenience. With regular maintenance, the building can achieve its design life with a minor frequency of damage and repair. The cost of building maintenance will increase yearly according to the inflation increase in each region. This study aims to analyze the maintenance costs of the Sports Center building using the LCC (Life Cycle Cost) method with architectural aspects (walls, ceilings, and floors) within the next 20 years. Life cycle costs (LCCs) are costs required by a building over the life of its plan. This approach assesses the total cost of an asset over its life cycle, including initial capital costs, maintenance costs, operating costs, and the residual value of an asset at the end of its life. The study's findings demonstrate how to create a model for predicting maintenance costs. According to this, the Sports Center building must spend IDR 1.445.082.148,15 on maintenance over the next 20 years. The following includes IDR 280.180.770,42 for ceiling maintenance, IDR 338.260.528,79 for walls, and IDR 826.640.848,94 for flooring.